Succinate and Lactate Production from Euglena gracilis during Dark, Anaerobic Conditions - Tomita, Yuko; Yoshioka, Kazumasa; Iijima, Hiroko; Nakashima, Ayaka; Iwata, Osamu; Suzuki, Kengo; Hasunuma, Tomohisa; Kondo, Akihiko; Hirai, Masami Yokota; Osanai, Takashi (Frontiers in Microbiology, 2016)
Euglena gracilis is a eukaryotic, unicellular phytoflagellate that has been widely studied in basic science and applied science. Under dark, anaerobic conditions, the cells of E. gracilis produce a wax ester that can be converted into biofuel. Here, we demonstrate that under dark, anaerobic conditions, E. gracilis excretes organic acids, such as succinate and lactate, which are bulk chemicals used in the production of bioplastics. The levels of succinate were altered by changes in the medium and temperature during dark, anaerobic incubation. Succinate production was enhanced when cells were incubated in CM medium in the presence of NaHCO3. Excretion of lactate was minimal in the absence of external carbon sources, but lactate was produced in the presence of glucose during dark, anaerobic incubation. E. gracilis predominantly produced L-lactate; however, the percentage of D-lactate increased to 28.4% in CM medium at 30°C. Finally, we used a commercial strain of E. gracilis for succinate production and found that nitrogen-starved cells, incubated under dark, anaerobic, produced 869.6 mg/L succinate over a 3-day incubation period, which was 70-fold higher than the amount produced by nitrogen-replete cells. This is the first study to demonstrate organic acid excretion by E. gracilis cells and to reveal novel aspects of primary carbon metabolism in this organism.